Alleviation of Submergence Stress in Rice Seedlings by Plant Growth-Promoting Rhizobacteria With ACC Deaminase Activity - Bal, Himadri Bhusan; Adhya, Tapan Kumar (Frontiers in Sustainable Food Systems, 2021)
Submergence stress slows seed germination, imposes fatalities and delays seedling establishment in rice. Seeds of submergence susceptible rice variety IR 42 were inoculated with four ACC utilizing isolates viz., Bacillus sp (AR-ACC1), Microbacterium sp. (AR-ACC2), Methylophaga sp. (AR-ACC3) and Paenibacillus sp. (ANR-ACC3) and subjected to submergence stress under controlled conditions for 7 days. Seeds treated with Microbacterium sp. AR-ACC2, Paenibacillus sp. ANR-ACC3 and Methylophaga sp. AR-ACC3 significantly enhanced the germination percentage (GP), seedling vigor index (SVI) and other growth parameters like root and shoot length and total chlorophyll contents, when compared with non-bacterized seeds submerged similarly. However, the values were statistically at par when control seeds were treated with AVG [L-α-(2-aminoethoxyvinyl) glycine hydrochloride], a known inhibitor of ethylene production. Results suggest that stress ethylene production was significantly reduced by around 85% in seedlings treated with Microbacterium sp. AR-ACC2 as compared to untreated control seeds under submergence. Paenibacillus sp. ANR-ACC3 and Methylophaga sp. AR-ACC3 were the next effective strains. Ethylene synthesis in seedlings was statistically at par with seeds treated with AVG suggesting ACC deaminase can effectively reduce ethylene levels in plants subjected to submergence. Bacillus sp (AR-ACC1) was neither able to significantly promote seedling growth parameters nor inhibit ethylene production as compared to control seeds. Results suggest that flooded soil planted to rice harbor microorganisms with plant growth promoting properties that can be used effectively to alleviate submergence stresses in susceptible rice varieties under field conditions